Predictive role of endogenous phase lags between target brain regions in dual-site transcranial alternating current stimulation - Osama Elyamany; Jona Iffland; Josef Bak; Cornelius Classen; Guido Nolte; Till R. Schneider; Gregor Leicht; Christoph Mulert (Brain Stimulation)
Background: Dual-site transcranial alternating current stimulation (tACS) provides a promising tool for modulating interregional brain connectivity by entraining neural oscillations. However, prior studies have reported inconsistent effects on connectivity and behavioral outcomes. They often focused on individualized stimulation-frequency as a key entrainment factor, while typically not focusing on the role of endogenous phase lags. To address this gap, we explored the predictive value of endogenous phase lags in dual-site tACS to modulate interhemispheric connectivity during dichotic listening. Methods: Thirty healthy participants (16 females) completed a dichotic listening task while undergoing simultaneous electroencephalography and tACS, including four bitemporal verum conditions with varying phase lags (0°, 45°, 90°, and 180°), and a sham condition across five sessions. Each session involved 20 min of 40-Hz tACS at a 0.5 mA peak-to-baseline amplitude applied to the temporal regions, with phase lags differing across sessions. Endogenous phase lags between the auditory cortices were calculated to explain changes in the laterality index (LI) across stimulation conditions by defining optimal and disruptive stimulation conditions for each participant. Results: Consistent with our hypothesis, our personalized analysis based on the calculated endogenous phase lags showed a significantly lower LI during the closest (optimal) stimulation condition compared to both the sham and farthest (disruptive) conditions. Conversely, the farthest stimulation condition did not statistically increase the LI compared to sham. Conclusions: These findings highlight the importance of incorporating endogenous phase dynamics into dual-site tACS protocols, paving the way for more consistent and individualized neuromodulatory interventions.